(untitled) (The Research of Medical Science Review, 2024)
Objective: To find the frequency of need of permanent pacemaker implant in patients of acute coronary syndrome with atrioventricular blocks. Study Design: Descriptive case series Place of Study: Department of cardiology, Punjab Institute of cardiology, Lahore during July to October 2024. Material and Methods: Total 200 patients of both genders presenting with atrioventricular blocks were included in the study. Demographic and medical history, including lifestyle factors and type of MI were noted. Patients were managed according to standard protocol and the need of permanent pacemaker implantation were assessed. Results: The mean age was 57.9%, 63% male vs 37% female. 38.5% had acute inferior wall myocardial infarction and 3 rd degree AB block was the most common conduction abnormality 53%. Pacemaker implantation was required in 21.5% of cases, with significant associations found between pacemaker need and factors like obesity, unstable angina, 3 rd degree AV block and ST changes (P<0.001). Conclusion: Need for permanent pacemaker implantation was important for patients with specific conduction abnormalities and cardiac condition. While factors like hypertension and life style have limited impact on pacemaker need.